ZAKAT AND ITS ROLE IN THE DEVELOPMENT OF COUNTRIES’ RESOURCES - JEHAD SALEH MHANNA (Journal of Islamic, Social, Economics and Development, 2019)
This study aims at studying the importance of Zakat and its role in the development of countries’ resources by following the analytical descriptive approach. The study focuses on some concepts related to Zakat in terms of its language and terminology and its importance in Islam, as well as the legitimacy of zakat and how to invest its money. In order to achieve the required development of the country’s resources, the necessary funding should be allocated to activate its role in every resource of the country. The researcher followed the analytical descriptive approach by describing concepts related to Zakat, how to invest it, and its importance in the development of state resources. Zakat is one of the development methods that fit our beliefs and Islamic values in the light of Quran and Sunnah and the actual economic and social conditions of our Islamic societies and the problems and constraints that confront us and in line with the changes in the different conditions to reach the comprehensive development in the country through finding productive projects for employment and providing basic needs. By this, it solves economic and social problems by reducing unemployment by increasing job creation, and its contribution to the distribution of wealth and income so as not to remain in the hands of a few.